Model Resource Sharing dan Kinerja Manajemen Sarana dan Prasarana - Yana Setiawan; Budhi Salira (Business Education Program of Universitas Pendidikan Indonesia, 2020)
Abstract. The problem in this research is that the management of facilities and infrastructure at Universitas Pendidikan Indonesia is not optimal. Operationally, the problem in this study is that optimal governance is managed with limitations in the academic services of the lecture classrooms. The formulation of the problem in this study is how to model resource sharing in the framework of optimizing the management of facilities and infrastructure at Universitas Pendidikan Indonesia. The purpose of this research is specifically to develop a resource sharing model in the framework of optimizing the management of facilities and infrastructure at the University of Pendidikan Indonesia. The results showed that strengthening resource sharing is needed for the Universitas Pendidikan Indonesia in order to optimize the management of facilities and infrastructure at Universitas Pendidikan Indonesia.Keywords: resource sharing, facilities; infrastructure Abstrak. Permasalahan dalam penelitian ini yaitu belum optimalya tata kelola sarana dan prasarana di Universitas Pendidikan Indonesia. Secara operasional permasalahan dalam penelitian ini yaitu belum optimalnya tata kelola digambarkan dengan masih adanya keterbatasan dalam layanan akademik ruang kelas perkuliahan. Rumusan masalah dalam penelitian ini yaitu bagaimana model resource sharing dalam rangka optimalisasi manajemen sarana dan prasarana universitas pendidikan indonesia. Tujuan penelitian ini secara khusus akan mengembangkan bagaimana model resource sharing dalam rangka optimalisasi manajemen sarana dan prasarana universitas pendidikan indonesia. Hasil Penelitian menunjukan bahwa penguatan resource sharing diperlukan bagi Universitas Pendidikan Indonesia dalam rangka optimalisasi manajemen sarana dan prasarana Universitas Pendidikan IndonesiaKata Kunci: berbagai sumber daya; sarana; prasarana